The Effect of O'clock Puzzle Playing Therapy on Cognitive Function in the Elderly in Nursing Home Area 3 Cirebon in 2023 - Amillah, Mala; Indah Permatasari, Leya; Nurapipah, Maulida (Jurnal Medisci, 2024)
Significant changes in the neurological system, which can lead to a decline in cognitive function, are shared among the aged. Giving puzzle play therapy to senior citizens is one way to enhance their cognitive abilities. This study aims to find out how O'clock Puzzle Play Therapy affects cognitive function in the elderly at Nursing Home Region 3 Cirebon in 2023. This study uses a pretest-posttest with a control group design and a proper experimental design. A total of 40 respondents make up the sample, which is obtained by complete sampling. They are employing the SPMSQ questionnaire to assess the cognitive abilities of the elderly. Univariate and bivariate data analysis was performed using the data normalcy test and the marginal homogeneity test. When older patients receiving o'clock puzzle play therapy were compared to those who did not get therapy, the results of the intellectual evaluation score using the SPMSQ showed a substantial rise. Four older adults from the intervention group (26.7%) who had severe cognitive impairment during the SPMSQ assessment prior to playing the o'clock puzzle therapy had severe intellectual impairment. In contrast, the number of older adults in the intervention group who had severe intellectual impairment decreased to zero. The study's findings, when combined with the Asymptotic value of the Marginal Homogeneity Test, indicate that o'clock puzzle play therapy impacts cognitive performance in the senior residents of the regional 3 Cirebon caring facility. 0.002 as the 2-tailed significance. Asymptotic value. Sig shows an Asymp in this study. The value difference is substantial when the sig value is less than 0.05.